Konseling Dengan Metode Sufisme (Jurusan Bimbingan dan Konseling Islam, 2020)
This study tries to explain about what and how the treatment of Sufism psychotherapy methods in counseling. The aim is to provide an additional discourse about Sufism psychotherapy in counseling as well as prevention, treatment (Curation) and self-care (development) in totality and perfection. This research uses a qualitative approach by applying library research methods. Literature-based research is a form of research that uses literature as an object of study. The analysis technique used is content analysis technique. Results of the study of Sufism psychotherapy methods include; Takhalli, Tahalli, and Tajalli.